(untitled) (Journal of the College of Basic Education, 2023)
University during 2010 to investigate the effect of salinity levels and growth regulators (Ethephon and Kinetin ) on germination of Coriandrum sativum , Lactuca sativa and Raphanus sativus seeds .The plants were grown under salinity levels (NaCl) of 0.0 , 2.5 , 5 and 10 ds/m . The seeds were soaked with concentration of ethephon (50, 75 and 100) ppm and Kinetin (1, 5 and 10) ppm while the control treatment was distilled water. The results showed that seed germination was significantly decreased as the salinity level increased up to 10 ds/m level. The results revealed that increasing salinity levels not only reduced seed germination but also decreased seed vigor traits which measured by (mean germination time and seed germination index ). Fresh and dry weight of seedling was significantly decrease as salinity level increased up to 10 ds/m comparing with control treatment. Soaking seed in ethephon or kinetin improved seed germination, seed and seedlings vigor under salinity levels comparing with the distilled water . The maximum increase in seed germination was obtained by soaking seeds with ethephon of 100 ppm and Kinetin 10 ppm .The results showed that treatment with ethephon at 100 ppm and Kinetin 10 ppm caused significant increase in fresh and dry weigh of seedling. Ethephon 75 ppm and Kinetin 10 ppm improved the seeds germination under salinization up to 10 ds/m . Ethephon at 100 ppm and 10 ds/m salinity showed a significant increase in seed germination 80% in Raphanus sativus. Kinetin at 10 ppm and 5 ds/m salinity was 90 % in Coriandrum sativum .